Local correlation and entropy maps as tools for detecting defects in industrial images - Skubalska-Rafajłowicz, Ewa (Zielona Góra: Uniwersytet Zielonogórski)
The aim of this paper is to propose two methods of detecting defects in industrial products by an analysis of gray level images with low contrast between the defects and their background. An additional difficulty is the high nonuniformity of the background in different parts of the same image.
Keywords: defects detection; image processing; local correlation; entropy map